Biodegradable nano-films for capture and non-invasive release of circulating tumor cells. (October 2015) - Li, Wei; Reátegui, Eduardo; Park, Myoung-Hwan; Castleberry, Steven; Deng, Jason Z.; Hsu, Bryan; Mayner, Sarah; Jensen, Anne E.; Sequist, Lecia V.; Maheswaran, Shyamala; Haber, Daniel A.; Toner, Mehmet; et al.
Abstract: Selective isolation and purification of circulating tumor cells (CTCs) from whole blood is an important capability for both clinical medicine and biological research. Current techniques to perform this task place the isolated cells under excessive stresses that reduce cell viability, and potentially induce phenotype change, therefore losing valuable information about the isolated cells. We present a biodegradable nano-film coating on the surface of a microfluidic chip, which can be used to effectively capture as well as non-invasively release cancer cell lines such as PC-3, LNCaP, DU 145, H1650 and H1975. We have applied layer-by-layer (LbL) assembly to create a library of ultrathin coatings using a broad range of materials through complementary interactions. By developing an LbL nano-film coating with an affinity-based cell-capture surface that is capable of selectively isolating cancer cells from whole blood, and that can be rapidly degraded on command, we are able to gently isolate cancer cells and recover them without compromising cell viability or proliferative potential. Our approach has the capability to overcome practical hurdles and provide viable cancer cells for downstream analyses, such as live cell imaging, single cell genomics, and in vitro cell culture of recovered cells. Furthermore, CTCs from cancer patients were also captured, identified, and successfully released using the LbL-modified microchips.